The Influence of Creativity And Training n Employee Performance Through Proactive Work Behavior At The Ministry Of Manpower - Puspita Mekar Sari; Osly Usman; Christian Wiradendi Wolor (ICON Publisher, 2026)
This study aims to analyze the influence of creativity and training on employee performance through Proactive Work Behavior (PWB) at the Ministry of Manpower of the Republic of Indonesia. The growing complexity of public services demands that civil servants not only perform routine tasks but also act innovatively and proactively. This quantitative research uses a survey method with 260 employees as samples, selected using proportionate random sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results show that creativity and training have a positive and significant direct effect on PWB and employee performance. Furthermore, PWB is proven to positively and significantly mediate the influence of creativity and training on employee performance. This study confirms the applicability of Social Cognitive Theory in the public sector and recommends that the Ministry foster a culture of innovation and proactive behavior to enhance bureaucratic reform and public service quality.